Interstitial lung disease associated with inflammatory myositis: Autoantibodies, clinical phenotypes, and progressive fibrosis - Ceribelli, Angela; Tonutti, Antonio; Isailovic, Natasa; De Santis, Maria; Selmi, Carlo (Frontiers in Medicine, 2023)
Progressive pulmonary fibrosis is generally diagnosed when interstitial lung disease progression occurs in the absence of any other cause, and a subset of patients with myositis and associated interstitial lung disease may develop progressive pulmonary fibrosis. Numerous autoantibodies (e.g., against tRNA-synthetase, MDA5, Ro52) increase the risk of this clinical feature in myositis and we speculate that serum biomarkers, sought using the most sensitive laboratory techniques available (i.e., immunoprecipitation) may predict pulmonary involvement and allow the early identification of progressive pulmonary fibrosis. We herein provide a narrative review of the literature and also present original data on pulmonary fibrosis in a cohort of patients with myositis and serum anti-Ro52 with interstitial lung disease. Our results fit into the previous evidence and support the association between anti-Ro52 and signs of pulmonary fibrosis in patients with inflammatory myositis. We believe that the combination of available and real-life data has significant clinical relevance as a paradigm of serum autoantibodies that prove useful in determining precision medicine in rare connective tissue diseases.